(3x+2y-1)5a=

Simple and best practice solution for (3x+2y-1)5a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+2y-1)5a= equation:


Simplifying
(3x + 2y + -1) * 5a = 0

Reorder the terms:
(-1 + 3x + 2y) * 5a = 0

Reorder the terms for easier multiplication:
5a(-1 + 3x + 2y) = 0
(-1 * 5a + 3x * 5a + 2y * 5a) = 0
(-5a + 15ax + 10ay) = 0

Solving
-5a + 15ax + 10ay = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '5a'.
5a(-1 + 3x + 2y) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(-1 + 3x + 2y)' equal to zero and attempt to solve: Simplifying -1 + 3x + 2y = 0 Solving -1 + 3x + 2y = 0 Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 3x + 1 + 2y = 0 + 1 Reorder the terms: -1 + 1 + 3x + 2y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 3x + 2y = 0 + 1 3x + 2y = 0 + 1 Combine like terms: 0 + 1 = 1 3x + 2y = 1 Add '-3x' to each side of the equation. 3x + -3x + 2y = 1 + -3x Combine like terms: 3x + -3x = 0 0 + 2y = 1 + -3x 2y = 1 + -3x Add '-2y' to each side of the equation. 2y + -2y = 1 + -3x + -2y Combine like terms: 2y + -2y = 0 0 = 1 + -3x + -2y Simplifying 0 = 1 + -3x + -2y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

a = {0}

See similar equations:

| 3r+24=7r | | 14(3s+4t)-(5s-3t)= | | -3m+4m+2=0 | | 3m+4m+2=0 | | 2(x-3)=-6+2x | | 3g-5=10 | | 60u-3(15u+8)= | | 4x-1=2(2x+5) | | (4a-7b)3ab= | | x(x^2+9x)= | | 4(14p-15q)= | | 2x^2+3x-94=0 | | 2x^2-3x+94=0 | | 2x+10=4x-2 | | 4x^2+16x-36=0 | | 4x+3=75 | | 17ab-5a-2ab-3a= | | 5k-5/k+1 | | 2x^2-14x-7=0 | | y=0.70x+7 | | 3(8g-2)=9(5g-10) | | 0.03(4c-56)=-0.6(c-2) | | 5h+5v=r | | 5h+5v=2 | | 0,185xx=43734 | | 0,47xx=141 | | 5t^2-16=16t | | x^2/6=11 | | 6x^2-35x+48=0 | | 2p^3-6p^2-20p=0 | | 4x-4=4m | | 18y^3-3y^2-9y=0 |

Equations solver categories